Impact of lung function decline on time to hospitalisation events in systemic sclerosis-associated interstitial lung disease (SSc-ILD): a joint model analysis - Kreuter, Michael; Del Galdo, Francesco; Miede, Corinna; Khanna, Dinesh; Wuyts, Wim A.; Hummers, Laura K.; Alves, Margarida; Schoof, Nils; Stock, Christian; Allanore, Yannick (Arthritis Research & Therapy, 2022)
Interstitial lung disease (ILD) is a common organ manifestation in systemic sclerosis (SSc) and is the leading cause of death in patients with SSc. A decline in forced vital capacity (FVC) is an indicator of ILD progression and is associated with mortality in patients with SSc-associated ILD (SSc-ILD). However, the relationship between FVC decline and hospitalisation events in patients with SSc-ILD is largely unknown. The objective of this post hoc analysis was to investigate the relationship between FVC decline and clinically important hospitalisation endpoints.